2022
DOI: 10.1364/ome.462695
|View full text |Cite
|
Sign up to set email alerts
|

Tuning and switching effects of quasi-BIC states combining phase change materials with all-dielectric metasurfaces

Abstract: Emission enhancement of quantum emitters is particularly relevant in the development of single-photon sources, which are key elements in quantum information and quantum communications. All-dielectric metasurfaces offer a route towards strong enhancement of local density of optical states via engineering of high quality factor optical modes. In particular, the recently proposed concept of quasi-bound states in the continuum (quasi-BIC) allows for precise control of such resonances in lattices with an asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…33 Furthermore, one can also employ various physical mechanisms to tune the metasurface transmission, 34 for example, using liquid crystals 35 or phase-change materials in combination with quasi-bound state in continuum (quasi-BIC) resonances. 36,37 We anticipate that our work will support the development of a new class of ultracompact and ultrasensitive flat meta-optical devices for a broad range of applications, including advanced sensing, imaging, and metrology in both classical and quantum photonics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…33 Furthermore, one can also employ various physical mechanisms to tune the metasurface transmission, 34 for example, using liquid crystals 35 or phase-change materials in combination with quasi-bound state in continuum (quasi-BIC) resonances. 36,37 We anticipate that our work will support the development of a new class of ultracompact and ultrasensitive flat meta-optical devices for a broad range of applications, including advanced sensing, imaging, and metrology in both classical and quantum photonics.…”
Section: Discussionmentioning
confidence: 98%
“…In the future, tilting the metasurface could serve as additional possibility to tune the polarization transformations 33 . Furthermore, one can also employ various physical mechanisms to tune the metasurface transmission, 34 for example, using liquid crystals 35 or phase-change materials in combination with quasi-bound state in continuum (quasi-BIC) resonances 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Recent realizations of BIC modulation via electrical, optical, or acoustical signals have been limited to on-off state switching or wavelength tuning of the state. [1,[6][7][8][9][10][11] Dynamic switching between BICs with different topological charges, a degree of freedom not yet unlocked, would offer new opportunities for switchable metasurfaces, integrated active nanophotonic devices, and tunable vector beams.…”
Section: Doi: 101002/adma202207430mentioning
confidence: 99%
“…Functional metasurfaces relying on phase-change media like chalcogenides, [10][11][12][13][14] metal-oxides, [15] and liquid crystals [9,16] offer solutions for dynamically tunable devices in a compact footprint. [17] However, while conventional phase-change media are widely exploited in passive reflective and transmissive devices, they are not suitable for active light emitting devices like lasers, due to the lack of optical gain.…”
Section: Doi: 101002/adma202207430mentioning
confidence: 99%
“…In particular, the refractive index of GST makes a large change through the phase transition. Based on the variation in the refractive index, GST has been combined with metasurfaces to generate numerous tunable optical devices. Recently, a few studies have demonstrated the tunable BICs by combining metasurfaces with semiconductor or polymer . However, the wavelength shift of quasi-BIC resonance is small (less than 20 nm) in these studies, , due to the little variation in the refraction index of semiconductor and polymer.…”
Section: Introductionmentioning
confidence: 99%